2022
DOI: 10.3390/land11060932
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Leguminous Cover Crops on Soil Chemical and Biological Properties in a No-Till Tropical Fruit Orchard

Abstract: South Florida’s agricultural soils are traditionally low in organic matter (OM) and high in carbonate rock fragments. These calcareous soils are inherently nutrient-poor and require management for successful crop production. Sunn hemp (SH, Crotalaria juncea) and velvet bean (VB, Mucuna pruriens) are highly productive leguminous cover crops (CCs) that have shown potential to add large quantities of dry biomass to nutrient- and organic-matter-limited systems. This study focuses on intercropping these two CCs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Even though we did not measure particulate organic matter, the patterns of labile organic C pools support this interpretation. Previous studies from the region reported SOM accumulation in 1 or 2 years after cover crop use; however, their soil sampling occurred shortly after the termination of cover crops, which could be prone to transient soil C dynamics due to the large C inputs from cover crop residues (Castellano-Hinojosa et al, 2022;Freidenreich et al, 2022;Wang et al, 2012). By tracking SOM concentrations prior to cover crop planting over 3 years, we were able to limit the transient effects of post cover crop termination and detect a temporal increase in soil SOM with cover crops, suggesting that continuous use of summer cover crops is likely to sustain SOM accumulation even in subtropical agroecosystems with coarse-textured soils.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we did not measure particulate organic matter, the patterns of labile organic C pools support this interpretation. Previous studies from the region reported SOM accumulation in 1 or 2 years after cover crop use; however, their soil sampling occurred shortly after the termination of cover crops, which could be prone to transient soil C dynamics due to the large C inputs from cover crop residues (Castellano-Hinojosa et al, 2022;Freidenreich et al, 2022;Wang et al, 2012). By tracking SOM concentrations prior to cover crop planting over 3 years, we were able to limit the transient effects of post cover crop termination and detect a temporal increase in soil SOM with cover crops, suggesting that continuous use of summer cover crops is likely to sustain SOM accumulation even in subtropical agroecosystems with coarse-textured soils.…”
Section: Discussionmentioning
confidence: 99%
“…Perennial cover crops are often used to improve soil properties of tropical fruit crops, even without the need to plow and incorporate the cover crop into the soil ( Wei et al, 2021 ; Freidenreich et al, 2022 ). However, they are more difficult to use in banana cropping systems compared to other tropical fruits, as banana leaves create a large amount of shade limiting the growth of most cover crops.…”
Section: Discussionmentioning
confidence: 99%
“…This practice likely contributed to soil improvement, potentially explaining the yield increase observed during that specific period. The studies (Freidenreich et al, 2022;Gou et al, 2023) have shown that incorporating leguminous plants into the soil as cover crops increases crop production. Prior to setting up the experiment, leguminous plants, which were used as cover crops in the field, were mixed with the soil just before the experiment, followed by barley planting.…”
Section: Changes In Grain Yieldmentioning
confidence: 99%